Tadeusz Dzierżykray-Rogalski – w siedemdziesiątą rocznicę urodzin - Drozdowski, Zbigniew (Anthropological Review, 2022)
The author presents the scientific output of professor Tadeusz Dzierżykray-Rogalski on his seventieth birth anniversary. The celebrator of the jubilee was for many years a chairman of the Polish Anthropological Society, the editor of the Polish Anthropological Review, a worthy scientist of the Polish Anthropology and organizer of the scientific life.